In situ relationships between microbiota and potential pathobiota in Arabidopsis thaliana - Bartoli, Claudia; Frachon, Léa; Barret, Matthieu; Rigal, Mylène; Huard-Chauveau, Carine; Mayjonade, Baptiste; Zanchetta, Catherine; Bouchez, Olivier; Roby, Dominique; Carrère, Sébastien; Roux, Fabrice (The ISME Journal, 2018)
A current challenge in microbial pathogenesis is to identify biological control agents that may prevent and/or limit host invasion by microbial pathogens. In natura, hosts are often infected by multiple pathogens. However, most of the current studies have been performed under laboratory controlled conditions and by taking into account the interaction between a single commensal species and a single pathogenic species. The next step is therefore to explore the relationships between host–microbial communities (microbiota) and microbial members with potential pathogenic behavior (pathobiota) in a realistic ecological context. In the present study, we investigated such relationships within root-associated and leaf-associated bacterial communities of 163 ecologically contrasted Arabidopsis thaliana populations sampled across two seasons in southwest of France. In agreement with the theory of the invasion paradox, we observed a significant humped-back relationship between microbiota and pathobiota α-diversity that was robust between both seasons and plant organs. In most populations, we also observed a strong dynamics of microbiota composition between seasons. Accordingly, the potential pathobiota composition was explained by combinations of season-specific microbiota operational taxonomic units. This result suggests that the potential biomarkers controlling pathogen’s invasion are highly dynamic.